EFFICIENCY ANALYSIS OF THE LIQUID CONTROLLER WITH A - BEAZIT Ali; Gheorghe SAMOILESCU (Fiabilitate şi Durabilitate)
This paperwork studies the efficiency of the liquid controllers with a ring valve analysing the liquidrunning through the controller, the variation of the pressure and its speed for various forms of the ring valvecontroller.